A review of the genus Bifidocoelotes Wang, 2002, with the description of three new species from China (Araneae, Agelenidae) - Liao, Rongrong; Wang, Ziwei; Yin, Haiqiang; Xu, Xiang (Zootaxa, 2022)
Three new species of the agelenid spider genus Bifidocoelotes Wang, 2002 are described from the mainland of China: Bifidocoelotes elongatus sp. nov. (♀; Guangxi, south China), B. mammiformis sp. nov. (♀, ♂; Guangdong, south China) and B. quadratus sp. nov. (♀; Guangxi, south China). The generic diagnosis is revised, and with the discovery of the three new species, the number of species in Bifidocoelotes doubles to six. Descriptions and illustrations of the three new species, a key to all the six species, and a distribution map for the genus are provided.